2015
DOI: 10.1002/cnma.201500010
|View full text |Cite
|
Sign up to set email alerts
|

Effective Use of Alkoxysilanes with Different Hydrolysis Rates for Particle Size Control of Aqueous Colloidal Mesostructured and Mesoporous Silica Nanoparticles by the Seed‐Growth Method

Abstract: The particle sizes of mesoporouss ilica nanoparticles most greatly affect their properties, including cellular uptake, cytotoxicity,a nd dispersity.T he growth of colloidal mesostructured silica nanoparticles (CMSS) with particle sizes lesst han 100 nm was controlled by am odified seedgrowth method by using alkoxysilanes (Si(OR) 4 ,R:M e, Et, Pr, and Bu) with different hydrolysis rates as additives. It was confirmed that the approximate matching of the hydrolysis rates of the added silanes with the consumption… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 95 publications
1
11
0
Order By: Relevance
“…These problems are discussed in detail for different silanes in refs. (Kang and Rhee 2005;Yamada et al 2012Yamada et al , 2015. Our results are in agreement with the findings presented in these papers.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…These problems are discussed in detail for different silanes in refs. (Kang and Rhee 2005;Yamada et al 2012Yamada et al , 2015. Our results are in agreement with the findings presented in these papers.…”
Section: Resultssupporting
confidence: 93%
“…Large alkoxy group diminishes the hydrolysis rate of silane. Yamada et al (2015) showed that the hydrolysis of TBOS needs more than 3 days and it is much longer than TEOS. Additionally, it should be noted that in our experiment, when TBOS is used as the silica source, silica beads are larger than those synthesized with TEOS.…”
Section: Resultsmentioning
confidence: 99%
“…In order to remove surfactants and TAB, a dialysis process was conducted in the same way as shown in our previous papers. [80][81][82][84][85][86][87] A colloidal suspension (50 mL) of one of the following ones (P-as, M-as, P_TIPBx-as, P_TMBx-as, or M_TIPB-as) was transferred into a dialysis membrane tube composed of cellulose (molecular weight cut off = 12 000-14 000) and dialyzed for 12 h against 250 mL of a mixture containing 2 M acetic acid and 2-propanol (1 : 1, v/v) and this process was repeated five times. Then the tube, which contained CMPS, was immersed in water to remove AcOH/ 2-PrOH from the tube, and the process was repeated twice.…”
Section: Removal Of Surfactants and Tab By A Dialysis Processmentioning
confidence: 99%
“…We reported that the addition of alkoxysilanes with different alkyl chain lengths is quite effective for the control of the particle size of colloidal MSNs smaller than 100 nm in size. 116,117 We also investigated the effect of alcohols on the size control of colloidal MSNs, and found that the addition of a hydrophobic alcohol leads to the enlargement of MSNs (Figure 11). 118 These methods are very useful for the precise control of the diameter of MSNs because only the hydrolysis rate can be tuned without drastically changing the condensation rate.…”
Section: Relationship Between Preparative Conditions Of Colloidal Msnmentioning
confidence: 99%